Study of different ratios of primary and waste activated sludges to enhance the methane yield. (15th September 2016) - Pinto, N.; Carvalho, A.; Pacheco, J.; Duarte, E.
Abstract: This work aimed the study of methane yield using different proportions of primary sludge (PS) and waste activated sludge (WAS) for anaerobic digestion (AD) conversion. Three trials were carried out: T1 (60 : 40, v/v), T2 (80 : 20, v/v) and T3 (100 : 00, v/v) to estimate the best proportion in comparison with a reference scenario, T0 (40 : 60, v/v). AD was performed in mesophilic conditions with a hydraulic retention time (HRT) of 15 days and an organic loading rate (OLR) expressed in total volatile solids (TVS) of 1.62 ± 0.06 kgTVS m −3 day −1 . Biogas production for trials T1 and T2 increased from 45 to 71% in comparison with T0. The experimental methane production along trials was used to assess the energy recovery corresponding to increases from 32 to 55%. The most suitable trial to be implemented at real‐scale is T1, applying a lower PS solid retention time combined with an increase of WAS thickening.